Education ou action sociale ? L’école dans la communauté, des community schools aux extended schools - Françoise Granoulhac (Revue LISA)
A concern for closer interactions between the school and the community has been part of the democratisation process in British education. Different patterns have emerged, based on a humanist and reformist view of society, or on a more radical and socially-committed approach. The extended schools concept draws on this tradition but signals a change of direction at a theoretical and political level. An examination of the extended schools programme reveals large discrepancies between an “inclusive” discourse taking up the community ideal and policies aiming first and foremost at tackling social ills.